2015
DOI: 10.1128/iai.02699-14
|View full text |Cite
|
Sign up to set email alerts
|

The Environment of “Mycobacterium avium subsp. hominissuis” Microaggregates Induces Synthesis of Small Proteins Associated with Efficient Infection of Respiratory Epithelial Cells

Abstract: "Mycobacterium avium subsp. hominissuis" is an opportunistic environmental pathogen that causes respiratory illness in immunocompromised patients, such as those with cystic fibrosis as well as other chronic respiratory diseases. Currently, there is no efficient approach to prevent or treat M. avium subsp. hominissuis infection in the lungs. During initial colonization of the airways, M. avium subsp. hominissuis forms microaggregates composed of 3 to 20 bacteria on human respiratory epithelial cells, which prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
54
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 29 publications
(54 citation statements)
references
References 53 publications
0
54
0
Order By: Relevance
“…Typhimurium (Diard et al, 2013), and a variety of mycobacterial species are reported to readily alter their phenotypes in response to external stimuli. The close relative of MAP, M. avium subspecies hominissuis, alters its phenotype upon the formation of microaggregates and biofilms (Babrak et al, 2015;McNabe et al, 2011), in response to the metal matrix found within host phagosomes (Early & Bermudez, 2011) and upon intracellular infection of macrophages and amoebae (Bermudez et al, 2004;Harriff & Bermudez, 2009 Patel et al, 2006). Our data suggest that MAP changes its phenotype during the stages of intracellular infection, and that these changes involve the alteration of whole cell-and cell wall-associated lipids.…”
Section: Discussionmentioning
confidence: 80%
“…Typhimurium (Diard et al, 2013), and a variety of mycobacterial species are reported to readily alter their phenotypes in response to external stimuli. The close relative of MAP, M. avium subspecies hominissuis, alters its phenotype upon the formation of microaggregates and biofilms (Babrak et al, 2015;McNabe et al, 2011), in response to the metal matrix found within host phagosomes (Early & Bermudez, 2011) and upon intracellular infection of macrophages and amoebae (Bermudez et al, 2004;Harriff & Bermudez, 2009 Patel et al, 2006). Our data suggest that MAP changes its phenotype during the stages of intracellular infection, and that these changes involve the alteration of whole cell-and cell wall-associated lipids.…”
Section: Discussionmentioning
confidence: 80%
“…17 Yamazaki et al, Babrak et al 2015, examined the initial interaction between MAH and respiratory epithelial cells and identified an invasive phenotype coupled with microaggregate formation when the bacteria were incubated with respiratory BEAS-2B bronchial epithelial cells for 24 hours as well as in vivo in a mouse model. 17,18 Subsequently, we genetically characterized the invasive microaggregate phenotype through DNA microarray, identifying highly regulated genes during microaggregate formation. 17 The protein, MAV_3013 (MBP-1) was identified as a surface-exposed, small protein, responsible for microaggregate attachment to the host epithelium through the interaction with the host intermediate protein, vimentin.…”
Section: Introductionmentioning
confidence: 99%
“…16 After adhering to the respiratory mucosa, there are several mechanisms in which the bacteria can form microaggregates: bacteria can replicate forming clonal microaggregates or bacteria can secrete extracellular signals to initiate recruitment of bacteria to the site of microaggregate formation. 15,17 MAH microaggregates consist of actively recruited planktonic bacteria, although a chemotactic substance or protein responsible for aggregation has not been elucidated. 17 Yamazaki et al, Babrak et al 2015, examined the initial interaction between MAH and respiratory epithelial cells and identified an invasive phenotype coupled with microaggregate formation when the bacteria were incubated with respiratory BEAS-2B bronchial epithelial cells for 24 hours as well as in vivo in a mouse model.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations